Overexpression of long non-coding RNA MEG3 suppresses breast cancer cell proliferation, invasion, and angiogenesis through AKT pathway - Chen-yu Zhang; Ming-sheng Yu; Xiang Li; Zhe Zhang; Ce-ran Han; Bo Yan (Tumor Biology)
Long non-coding RNA MEG3 has been identified as a tumor suppressor which plays important roles in tumorigenesis; however, its potential role in breast cancer has not been fully examined. Here, we showed that MEG3 was downregulated in breast cancer tissues and cell lines. Overexpression of MEG3 inhibited breast cancer cell proliferation and invasion, suggesting that MEG3 played an important role in breast cancer progression and metastasis. Moreover, MEG3 upregulation caused marked inhibition of angiogenesis-related factor expression. Conditioned medium derived from MEG3 overexpressed breast cancer cells significantly decreased the capillary tube formation of endothelial cells. Furthermore, elevated expression of MEG3 in breast cancer inhibits in vivo tumorigenesis and angiogenesis in a nude mouse xenograft model. Mechanistically, overexpression of MEG3 results in downregulation of AKT signaling, which is pivotal for breast cancer cell growth, invasion, and tumor angiogenesis. Collectively, these results suggest that MEG3 might suppress the tumor growth and angiogenesis via AKT signaling pathway and MEG3 may serve as a potential novel diagnostic and therapeutic target of breast cancer.